Developing a sharia compliance e-commerce trust framework - Ribadu, Mohammed Bashir (2019)
Over the years, e-commerce has transformed the conduct of business processes, marketplaces, and relationships among its various stakeholders. The growth of ecommerce has been rapid and stimulated by its numerous benefits which attract businesses and consumers to adopt. However, there are serious concerns among many Muslims over the non-Sharia compliance of the prevailing e-commerce systems which results in reluctance and abstinence to patronise, largely due to lack of trust. Yet, the factors that influence Muslim consumer perception of Sharia compliance e-commerce (SCE-C) trust have not been adequately studied. Furthermore, comprehensive and clearly specified Sharia compliance requirements for e-commerce systems are lacking, and a constraint to determine the SCE-C quality factors that can foster SCE-C trust. Therefore, this study is carried out to develop an SCE-C trust framework that consists of factors that have a positive influence on the Muslim consumer perception of SCEC trust. This process involves developing a Sharia compliance requirements framework that will provide a clear guideline for e-commerce systems. Consequently, to determine the SCE-C Quality factors and finally, the SCE-C trust framework. A mixed research method involving qualitative and quantitative approaches was adopted in this study. It involved an exploratory sequential design that structured the study into three successive phases. The first phase was to find the SCE-C requirements through semi-structured interviews with eight Sharia compliance experts in Malaysia. Therefore, the data were analysed using content analysis technique with the aid of Nvivo11. Consequently, SCE-C quality factors and an SCE-C trust framework was successively developed and validated through a quantitative and confirmatory approach. The study collected 451 valid responses from Muslim participants using self-administered questionnaires within four university campuses in Malaysia. The data were subjected to exploratory and confirmatory factor analysis, and structural equation modelling with the aid of IBM SPSS 23 and Amos 23 respectively. Therefore, the factor structure, model fitness, convergent and discriminant validity, construct reliability, and hypothesized paths of the SCE-C quality and the SCE-C trust models were tested. Fundamentally, the proposed SCE-C trust framework was found to be supported. The SCE-C trust factors revealed are SCE-C quality, Islamic commitment, and trust propensity which has a direct, positive, and significant influence on the Muslim consumer perception of SCE-C trust. Although, SCE-C quality was found to be the most significant factor that influences Muslim consumer perception of SCE-C trust. Therefore, SCE-C trust framework provides e-commerce stakeholders with an insight on the factors that influence Muslim consumer perception of SCE-C trust. The SCEC quality factors (phase 2) consists of information accuracy, information completeness, devoid of haram, usability, customization, security, and service quality. Whereas, the SCE-C requirements (phase 1) stipulates that, e-commerce systems must adhere to the maqasid Sharia essentials of enhancing maslaha (welfare) of society and the Islamic law of contract. Primarily, Islam permits and indeed encourage Muslims to partake in e-commerce as long as it is Sharia compliant.